THE INFLUENCE OF DIFFERENCE TEMPERATURE AGAINST THE RATE OF EMBRYONIC DEVELOPMENT AND LARVAL ABNORMALITY OF CANTIK GROUPER (EPINEPHELUS SP.) - Simbolon, Aprisianus Julkarman; Sutarjo, Ganjar Adhywirawan; Hariyadi, Hariyadi (xxxx-xxxx)
Cantikgrouper is the hybridization results grouper or cross-breeding between Epinephelus fuscoguttatus as a female and Epinephelus microdon as a male. The main barriers faced in the development of this commodity is still low levels of spawning up to seeding grouper. Based on the background, this study aimed to investigate optimum temperature observations against the rate of embryonic development Epinephelus sp.larvae. This study used the results of artificial spawning eggs.The fertilized eggs were incubated on six pieces of the container temperature treatment;each treatment there was repeated three times.The incubation temperature was kept on (A) 21-22°C; (B) 23-24°C; (C) 25-26°C; (D) 27-28°C; (E) 29-30°C; (F) 31-32°C. Results showed that eggswere incubated at a temperature of 21-22 ? embryonic development to a halt in the blastula, and temperature 23-24°C stalled on phasemyomere embryos. The low-temperature incubation period lasts a long time. Temperature 25-26°C needed 18 hours 6 minutes by 8.33% abnormality rate. Temperature 27-28°C needed 16 hours to hatch witha degree of abnormality of 7.6%. Temperature 29-30°C needed 15 hours 1 minute for the hatch tothe degree of abnormality of 5.33%. The 31-32°C temperature needed 14 hours 6 minutes to hatch witha degree of abnormality of 17.3%. The limits of tolerance for the incubation of the eggs ofcantik grouper (Epinephelusspp.) were 26-32°C.The best temperature of each treatment were obtained at a temperature of 29-30°C. Based on our results, it concluded that the changing temperature affected how long eggs could hatch.